the EFEKTIVITAS KONSUMSI DAUN UBI JALAR UNGU TERHADAP PENINGKATAN KADAR HEMOGLOBIN DARAH IBU HAMIL TRIMESTER PERTAMA - Luh Putu Yuliastuti; Fitri Setianingsih; Nurlaila Agustkawati (Jurnal Ilmu Kebidanan, 2022)
One of the highest causes of maternal mortality in Indonesia is caused by bleeding which is indirectly caused by anemia in pregnant women. The need for iron in pregnant women will increase, but the administration of Fe tablets sometimes causes side effects of nausea and vomiting for pregnant women, resulting in non-compliance of pregnant women in consuming them. This study aims to determine the effectiveness of increasing the Hb of pregnant women in the first trimester by consuming sweet potato leaves. This research method uses pre-experimental with one group only pretest-posttest. Based on the result of the t-test analysis, the value tcount < ttable (-11.19 <-2.262) with a significant value (0.000) < 0.05, which means that there is a difference in blood hemoglobin levels of pregnant women in the first trimester before and after consuming purple sweet potato leaves. This can be interpreted than consuming purple sweet potato leaves can effectively increase blood hemoglobin levels of pregrant women in the first trimester. Judging from the average N-gain value is 1.056 > 0.7, it can be concluded that the comsumption of purple sweet potato leaves to increase blood hemoglobin category. Based on this analysis, sweet potato leaves can be consumed daily as a companion to Fe tablets for pregnant women.